Study On Properties Of Binderless,Particleboard From Oil Palm (Elaeis Guineensis) Biomass - Nadhari, Wan Noor Aidawati Wan (2011)

(untitled)
Binderless panels were manufactured from the particles of bark, leaves, fronds, middlepart and core-part of oil palm trunks at two different target densities (0.8 g/cm3 and 1.0g/cm3) using two different pressures (5 MPa and 12 MPa). Binderless panels produced were tested for the physical and mechanical properties. Chemical analysis had also been conducted including determination of extractives, holocellulose, alpha-cellulose, lignin content, starch content, individual sugar, and total sugar content in oil palm fibers.